2015
DOI: 10.1371/journal.pone.0141605
|View full text |Cite
|
Sign up to set email alerts
|

Study on Market Stability and Price Limit of Chinese Stock Index Futures Market: An Agent-Based Modeling Perspective

Abstract: This paper explores a method of managing the risk of the stock index futures market and the cross-market through analyzing the effectiveness of price limits on the Chinese Stock Index 300 futures market. We adopt a cross-market artificial financial market (include the stock market and the stock index futures market) as a platform on which to simulate the operation of the CSI 300 futures market by changing the settings of price limits. After comparing the market stability under different price limits by appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Xu et al [41] constructed an artificial spot-futures market model with crossmarket traders and successfully reproduced the typical characteristics of Chinese stock market and the CSI 300 index futures market. After that, Xiong et al [42]; Liang et al [43], and Xiong et al [44] did further research based on the model of Xu et al [41]. Xiong et al [42] focused on the price limits level in futures market and found that enhancing or removing price limits could both hurt market stability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Xu et al [41] constructed an artificial spot-futures market model with crossmarket traders and successfully reproduced the typical characteristics of Chinese stock market and the CSI 300 index futures market. After that, Xiong et al [42]; Liang et al [43], and Xiong et al [44] did further research based on the model of Xu et al [41]. Xiong et al [42] focused on the price limits level in futures market and found that enhancing or removing price limits could both hurt market stability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang, Ping, Zhu, Li, and Xiong () use an artificial stock market model to measure the effect of circuit breakers, whereas Xiong, Nan, Yang, and Yongjie () employ an agent‐based model to do the same. Lin () proposes a theoretical framework for capturing tail behaviour of volatility under price limits and demonstrates its effectiveness in measuring dynamic spillover effects.…”
Section: Future Research Avenuesmentioning
confidence: 99%
“…Second, the equity returns of firms operating in oil exploration, refinery, and marketing are co-integrated with the one-month and four-month oil futures prices [ 27 , 28 ]. Third, as concluded by [ 21 , 29 ], the variability of the futures prices is a judgment of the efficiency of hedging activities of firms engaged in hedging. However, considering the fact that the majority of previous studies have preferred using the spot price [ 30 32 ], we use both the spot and the futures prices data, similar to [ 33 ].…”
Section: Data Descriptionmentioning
confidence: 99%